Pharmacokinetics of 14C‐ortho‐phenylphenol following intravenous administration in pigs. Issue 4 (4th September 2016) - Nixon, Emma; Brooks, James D.; Routh, Patricia A.; Chittenden, Jason T.; Baynes, Ronald E.
Abstract: Workers in the USA are exposed to industrial formulations, which may be toxic. These formulations often contain preservatives or biocides such as ortho‐phenylphenol (OPP). There are limited data describing OPP following intravenous administration to assess truly the clearance of this chemical in humans and other species. In vivo experiments were conducted in pigs to determine related pharmacokinetic parameters. 14 C‐OPP was administered as an intravenous bolus dose. Blood, feces, urine and tissue samples were collected for analysis by liquid scintillation. Data were analyzed using non‐compartmental and compartmental pharmacokinetic model approaches. These data fitted a three‐compartment model and showed that the half‐life of 14 C‐OPP following the intravenous bolus in pigs was 46.26 ± 10.01 h. The kidneys play a crucial role in clearance of 14 C‐OPP with a large percentage of the dose being found in the urine (70.3 ± 6.9% dose). Comparisons with other species suggest that 14 C‐OPP clearance in pigs (2.48 ml h –1  kg –1 ) is less than that in humans (18.87 ml h –1  kg –1 ) and rats (35.51 ml h –1  kg –1 ). Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Ortho‐phenylphenol (OPP) is an antimicrobial agent with varied uses. Blood, feces, urine and tissue samples were analyzed by liquid scintillation following an intravenous bolus of 14 C‐OPP in pigs. A three‐compartment model showed that the half‐life was 46.26 h. The kidneys play a crucial role in the clearance of 14 C‐OPP with 70.3% dose found in urine. 14 C‐OPP clearance in pigs (2.48 ml h −1  kg −1 ) is less than that in humans and rats (18.87 and 35.51 ml h −1  kg −1 respectively).